Severe Lymphopenia Is Associated with Elevated Plasma Interleukin-15 Levels and Increased Mortality During Severe Sepsis. Issue 6 (June 2015) - Chung, Kuei-Pin; Chang, Hou-Tai; Lo, Shyh-Chyi; Chang, Lih-Yu; Lin, Shu-Yung; Cheng, Aristine; Huang, Yen-Tsung; Chen, Chih-Cheng; Lee, Meng-Rui; Chen, Yi-Jung; Hou, Hsin-Han; Hsu, Chia-Lin; et al.
<x xml:space="preserve">Abstract</x> ABSTRACT Sepsis-related mortality has been found increased in RAG-1 knockout mice. However, in patients admitted to medical intensive care units, it is unknown whether severe lymphocyte depletion at admission is associated with increased interleukin (IL)-7 and IL-15 levels in circulation, and increased mortality. We prospectively enrolled 92 patients who were admitted to medical intensive care units for severe sepsis or septic shock. At admission, 24 patients (26.1%) had severe lymphopenia, defined as lymphocyte counts of less than 0.5 × 103/μL. Severe lymphopenia was associated with significantly higher plasma levels of tumor necrosis factor α, IL-6, IL-8, and IL-10 and was also independently associated with 28-day mortality (adjusted hazard ratio, 3.532; 95% confidence interval, 1.482−8.416; P = 0.004). The levels of plasma IL-15, but not IL-7, were increased modestly in patients with severe lymphopenia compared with those without (median, 12.2 vs. 6.4 pg/mL; P = 0.005). The elevated plasma IL-15 levels were contrarily associated with significantly decreased B-cell lymphoma 2 mRNA expression in peripheral blood mononuclear cells. In conclusion, severe lymphopenia was associated with increased mortality in patients with severe sepsis. We found that patients with sepsis with severe lymphopenia had down-regulated B-cell lymphoma 2 mRNA expression in peripheral blood mononuclear cells, despite increased plasma IL-15 concentrations. Whether IL-7 and IL-15 are insufficient in patients with severe lymphopenia during severe sepsis warrants further investigations.